Analysis Of Serum Cystatin C Levels In People With Type 2 Diabetes Mellitus As A Biomarker Of Early Detection Of Atherosclerosis - Misnarliah; Anastasia A. Basir; Zainuddin (Publisher Cv. Inara, 2021)
Type 2 diabetes mellitus (DMT2) is associated with atherosclerosis, which causes the disease. cardiovascular and increased mortality. It is still difficult to detect ateroskelerosis in the early stages. Arterial stenosis often develops without symptoms in patients. DMT2, then causes cardiovascular disease. Therefore, development diagnostics to easily detect early-stage atherosclerosis are needed. In this study, we focused on cystatin C serum, an inhibitor of cysteine proteinase. Some research results, it has reported a significant correlation between serum Cystatin C levels and Arterial stiffness in a group of normal individuals. Cystatin C serum has a correlation strong with a value of elasticity of the carotid artery walls that reflect the degree of atherosclerosis subclinical. This is a new sign that is quite potential as a biomarker of early detection atherosclerosis. The purpose of the study is to know the picture serum Cystatin C levels as an early marker to determine the presence of possible complications of atherosclerosis in DMT2 patients, as well as the usefulness of Cystatin-C in predicting atherosclerosis of the early stages. Research methods are analytical research with use cross-sectional design. The study was conducted by calculating the value of Cystatin C blood serum with DMT2. The study subjects were people with DMT2 in RSUD.Labuang Baji Makassarand its network. Sum the sample in this study was 20 people. Determination of the research subject is done by conducting a search on medical records of DMT2 patients who meet the criteria of inclusion and exclusion to achieve minimum number of samples. The study subjects were classified into two groups based on medical record data searches are subclinical atherosclerosis group and nonclinical group ateroskelorosis. The research sample is a serum sample. Serum sample examination is carried out in the Clinical Prodia Laboratory using PENIA method. The results of this study reported the results that Cystatin-C Serum is closely correlated with subclinical atherosclerosis (arterial stiffness. Increase in serum cystatin-C levels indicates the risk of atherosclerosis in Patients with DMT2. The results of this study reported that serum cystatin C levels in dmt2 patients in the nonclinical atherosclerosis group (n = 10) showed normal cystatin levels (0.50 - 0.96 mg/L), while serum Cystatin-C levels in dmt2 group patients showed normal cystatin levels (0.50 - 0.96 mg/L), while serum cystatin-C levels in DMT2 group patients Subclinical atherosclerosis (n = 10) has an increase in serum cystatin-C levels (> 0.90 mg/L). Level cystatin C serum is associated with SA in DMT2 patients. Cystatin C was identified as a predictor of atherosclerosis risk, after adjusting for a variety of factors associated with diabetes.